Measuring Intravascular Migration of Mouse Ly6Clow Monocytes In Vivo Using Intravital Microscopy. (15th April 2013) - Carlin, L.M.; Auffray, C.; Geissmann, F.
Abstract: This unit describes methods for intravital imaging of monocytes in the vasculature of the dermis and the mesentery in vivo using fluorescent reporter mice, fluorescent dyes, and antibodies. Cx3cr1 gfp/gfp (or +), Rag2 −/−, Il2rg −/− mice expressing eGFP at the locus of the Cx3cr1 gene, on the Rag2 −/− Il2rg −/− C57Bl/6 background, are used. Although aimed at specifically tracking Ly6C low monocytes, these protocols could readily be adapted to investigate the interaction of other blood leukocytes with the vascular endothelium by use of other fluorescent reporter mice and fluorescently labeled antibodies. Curr. Protoc. Immunol . 101:14.33.1‐14.33.16. © 2013 by John Wiley & Sons, Inc.